Controversial risk factors for cholangiocarcinoma. Issue 3 (March 2022) - Baidoun, Firas; Sarmini, Muhammad Talal; Merjaneh, Zahi; Moustafa, Muhamad Alhaj
Abstract : Introduction: Cholangiocarcinoma is a rare malignancy accounting for 3% of gastrointestinal cancers in the USA. While multiple risk factors for cholangiocarcinoma are established, other potential risk factors are still controversial. Herein, we used a large national database to investigate possible risk factors and associations. Method: We used the National Inpatient Sample database to review all admissions between 2011 and 2015. We grouped patients based on the presence and absence of cholangiocarcinoma. Using multivariate logistic regression analysis, we assessed the association between obesity, alcohol abuse, smoking, diabetes mellitus and cholangiocarcinoma. Results: Out of 30 9552 95 admissions, 20 030 had cholangiocarcinoma. Cholangiocarcinoma patients were older (67 ± 12.8 vs. 57 ± 20.6; P  < 0.001) and had fewer female patients (48 vs. 59%; P  < 0.001). Multivariate logistic regression analysis showed that diabetes mellitus was associated with cholangiocarcinoma (OR, 1.04; 95% CI, 1.01–1.08; P  < 0.001). On the other hand, alcohol, smoking and obesity were all inversely associated with cholangiocarcinoma (OR, 0.75; 95% CI, 0.69–0.81; P  < 0.001), (OR, 0.75; 95% CI, 0.71–0.79; P  < 0.001) and (OR, 0.71; 95% CI, 0.67–0.75; P  < 0.001), respectively. In addition, compared to Whites, Hispanic and Asian/Pacific Islander races were more associated with cholangiocarcinoma (OR, 1.27; 95% CI, 1.21–1.34) and (OR, 1.79; 95% CI, 1.67–1.92) ( P  < 0.001 for all), respectively, whereas African American race was inversely associated with cholangiocarcinoma (OR, 0.85; 95% CI, 0.81–0.89; P  < 0.001). Conclusion: Patients with a diagnosis of diabetes mellitus or from certain ethnic groups (Hispanic and Asian/Pacific Islander) are associated with increased risk for cholangiocarcinoma. Abstract : Supplemental Digital Content is available in the text.